(untitled) (Architecture Image Studies, 2026)
The current study provides an exhaustive insight into the progressive failure modes of Fiber-Reinforced Polymer (FRP) laminates, especially delamination. Using progressive failure analysis (P.F.A.) analysis within a Finite Element Method framework. A detailed of numerical modeling approach was employed that tracked specific failure chronologies, including first ply failure (FPF), delamination initiation, and ultimate failure, for configurations like open-hole tension (O.H.T.) specimens and laminates with different stacking sequences, in addition, energy dissipation predictions quantified the contributions of different failure modes, such as fiber fracture/kinking and matrix cracking/crushing and in-plane shear failure and Mode I/II/III delamination. The effect of stacking sequence optimization on delamination resistance and overall structural performance was investigated through parametric studies. The P.F.A. model predictions were also compared with simplified analytical models and fictitious test data, showing notably better ability to capture the multiple coupling of damage modes. the findings reveal that delamination acts as an interacting and potentially life-limiting failure mode and can provide substantial guidance for the composite design optimization and structural reliability improvements.